MINIMARKET APPLICATION WITH VISUAL BASIC 6.0 - Candra Ari Yanto; Hariyanto.,Skom.,MMSI Hariyanto.,Skom.,MMSI (Jurnal Sistem Informasi, 2010)
Market is the place of sale and purchase transactions, in transactions conducted incash a lot of things that need to be considered by the seller and buyer, in order toreach an agreement and the benefits for both parties. One type of modern marketsthere is a mini business. In order to mini business can run well and transactionsbecome more effective, efficient and profitable. We need a sales application that canhelp solve those problems.Therefore, the author makes the writing of the title Minimarket Applications WithVisual Basic 6.0, which was created by using Microsoft Visual Basic 6.0 andMicrosoft Access for the database.